The Factors Causing Incomplete Inpatient Medical Records at Pringsewu Regional Public Hospital - siti rohana; Sigit Andriyanto; Yessiana Luthfia Bahri; Etanaulia Marsim (UrbanGreen, 2026)
Incomplete medical records can reduce the quality of healthcare services, hinder clinical decision-making, and increase legal risks. At the Regional Hospital of Pringsewu, 112 out of 580 inpatient medical record files from the Women's Internal Medicine Unit were found to be incomplete during May–July 2025. The study involved four main informants, with the Head of Medical Records and Medical Records Officer serving as triangulation informants. The findings revealed that the man factor was the most dominant cause, including low discipline, high workload, limited time, and lack of training. Method factors included the absence of specific SOPs, routine evaluations, and reward or sanction systems. Machine factors involved inadequate information technology facilities and unstable internet connectivity. Hospitals should strengthen training and evaluation programs and implement reward and sanction systems to improve medical record completeness and accuracy